Conversor ANPC com porta CC bidirecional secundária para conexão de sistemas de armazenamento de energia - Teston, Silvio Antonio (2020)
This doctoral dissertation presents a new multilevel converter topology, derived from the ANPC inverter, which allows the connection of energy storage systems directly to the topology in a secondary DC port. In this way, the use of a DC-DC or DC-AC converter dedicated to processing the energy of the storage system is avoided. In the proposed topology, each leg of the ANPC inverter has three ports: the main DC port (common to all legs), the secondary DC port, and the AC port. The inclusion of a secondary DC port is allowed due to the existence of redundant conduction states that can generate two different voltage levels in the secondary DC port. Also, a detailed study of the conduction states and their switching interactions is presented together with proposals for the simultaneous modulation of the AC port and the secondary DC port by using a carrier-based approach. Four converter modulation strategies, using two carrier arrangement options, and two switching sequences are analyzed. The analysis and proposal of a control system for a grid-connected application are also performed. This control system can regulate the power ports currents while keeping the average voltages of the DC bus poles balanced. A single-phase half-bridge prototype of 1-kW was built and tested in the laboratory to prove the operation of the proposed topology in all operating modes. Results of the steady-state and transient responses and measurements of the converter performance in the main modes of operation, considering two modulation strategies of the secondary DC port, are presented. The modulation strategy with type 2 sequence presented the best results in terms of efficiency and quality of the ESS current. These results are mainly due to the lack of type III commutations in this modulation strategy. The maximum efficiency of 96.3% was obtained in the ESS recharge mode and modulation with type 2 sequence. The current injected into the grid showed a maximum total harmonic distortion of 5% and a DC component below 10 mA.